New postmortem diagnostic biomarker for myocardial infarction: ischemia modified albumin - Yagmur, Fatih; Celik, Safa; Cemek, Mustafa; Hazini, Ahmet; Kocaman, A. Tuba; Alpdogtas, Saadet; Konak, H. Busra; Yildirim, Muzaffer; Celtek, Mustafa (TAYLOR & FRANCIS LTD, 2019)
We investigated the change of IMA levels as biochemical markers, especially in the postmortem diagnosis of early MI. Also, histological investigation has been performed in cases of cardiac deaths and in non-cardiac cases. To the best of our knowledge, this is the first study to investigate the levels of IMA in the postmortem diagnosis of early MI. A series of medicolegal autopsy cases (n=139; 6-24 h postmortem, with a median of 16 h) were examined at our institute. The cases comprised 112 males and 27 females, between 16 and 89 years of age. Subjects were divided into six groups depending upon their final cause of death according to medical data, autopsy reports, biochemical and histological findings. The groups were as follows: cardiovascular disease, blunt trauma, asphyxia, pathological cerebral hemorrhage, bleeding due to a sharp object and gunshot injuries, and poisoning. IMA levels in the cardiovascular disease group were found to be significantly higher than the blunt trauma, asphyxia, pathological cerebral hemorrhage, and bleeding groups (p < 0.05). It is known that after MI, if less than 4-6 hours pass before death, the histopathology of the heart does not reveal significant findings. Our results demonstrated that IMA might be a valid biochemical marker, especially in the postmortem diagnosis of early MI.
Keywords: Myocardial infarction; ischemia modified albumin; postmortem biochemistry; diagnostic biomarker; forensic pathology; cause of death; CARDIAC TROPONIN-I; CREATINE-KINASE MB; PERICARDIAL FLUID; MARKERS; LDH; CK; Legal Medicine